A Comparison Study of Spinal Anesthesia with General Anesthesia in Cesarean Section - Rajeev Kumar Das; Manu Seth (Academia Anesthesiologica International, 2019)
Background: The present study was conducted to compare spinal anesthesia with general anesthesia in cesarean section. Subjects and Methods: The present study was conducted in the department of Anesthesiology. It comprised of 78 pregnant women with American Society of Anaesthesiologists (ASA) physical status grade I or II who were scheduled to undergo elective CS under SA. Patients were divided into 2 groups. In both groups, side-effects after surgery such as nausea, vomiting, headache, pain and other clinical symptoms were noted. Results: The mean WBC count in group I was 12.74 109/L and 10.62 109/L in group II which was significant (P< 0.05). Other parameters such as mean RBCs, mean hemoglobin and mean platelet count was non- significant (P> 0.05). In group I most common complication was fever (6) and hypotension (6) while in group II, fever (8) and hypotension (7). However, the difference was non- significant (P> 0.05). Conclusion: Both spinal anesthesia and general anesthesia showed variations in hematological parameters as well as complications.